OBSERVAÇÕES SÔBRE PLANTAS INVASORAS NOS TALHÕES DE Eucalyptus robusta SM. - Piccolo, A. Lélia G.; Silva, Edena M. P. da; Lelis, Gislane J.; Ramos, Merilene R.; Kachan, Myriam S. (REVISTA DE AGRICULTURA, 2016)
OBSERVAÇÕES SÔBRE PLANTAS INVASORAS NOS TALHÕES DE Eucalyptus robusta SM.